Ontological Approach to the Document Synthesis Based on Data Mining - Borisov, V.V.; Misnik, A.E.; Sharaburka, A.M.; Zakharchenkov, K.V. (2024 7th International Conference on Information Technologies in Engineering Education (Inforino), 2024)
This article presents a comprehensive study on the utilization of data mining technologies and ontological approaches in the field of government procurement. It highlights the complexities involved in defining procurement object requirements and developing technical specifications, which vary significantly from case to case. The study underscores the need for procurement professionals to possess extensive knowledge across various sectors due to the diversity of goods, works, and services procured. The adoption of Intelligent Data Analysis is proposed as a solution to enhance the accuracy and efficiency of procurement processes. The research investigates the potential of automating ontology construction to facilitate decision-making in creating technical specifications. It examines the legal framework governing government procurement and explores the capabilities of the Unified Information System for public procurement in Russia. The paper also describes the development of a typed ontology for public procurement, emphasizing the importance of an ontological approach in managing the large volume of multistructured information typical in procurement documentation. This approach is vital for the automated synthesis of necessary documents, offering significant support in decision-making processes. The article concludes with a detailed exploration of the ontological approach to document synthesis in government procurements. It outlines the process of selecting procurement subjects, conducting intellectual analysis of texts, and using intelligent data analysis techniques to ensure compliance with legal requirements.